IMPACT OF COMMUNITY SUPPORT ON THE GROWTH OF FEMALE ENTREPRENEURS DURING COVID-19 SITUATION” - Dr. Dipesh Daddelal Uike, Mr. Gangesh Mahesh Gupta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The COVID-19 has suffered the whole world’s people collectively. Rich and poor, Manager and Labour, or Entrepreneurs and employees, everyone has suffered in this pandemic situation. COVID-19 has made people very weak and helpless. The very poor situation is of small entrepreneurs who are badly hit by the situation and struggling to survive their business. When the whole world is facing COVID-19 situation which has very badly hit the market, under this situation the women entrepreneurs are very close to shut down their businesses. COVID-19 has inclined the women more to the family than the business. Stay at home and lockdown have increased their responsibilities towards home and children and made available very limited time for the business. Total 510 small female entrepreneurs are taken for the study, who are running their business in Mumbai city. Two-way ANOVA and multiple regression tools are used for data analysis. The research study has shown that there was a great impact of community support on the female entrepreneurs’ growth. COVID-19 pandemic has minimised the support of spouse and other entrepreneurs. This support was more before pandemic. In pandemic crisis other entrepreneurs’ network have given more support to the female entrepreneurs than spouse support for their business.